Genetic and phenotypic characteristics of Klebsiella michiganensis isolates - E. P. Sivolodskii (Sankt-Peterburg : NIIÈM imeni Pastera, 2020)
The aim of the study was to identify an optimal research target for detection of Klebsiella michiganensis isolates, determine their genetic and phenotypic characteristics necessary for identification. Here, we examined 11 Klebsiella oxytoca strains, lacking (atypical, negative) a marker 5-aminosalicylate decarboxylase (detected by the chromogenic reaction by 5-aminosalicylic acid) unique for the genus Klebsiella bacteria. They were selected for genetic analysis subsequent to a phenotypic characterization of K. oxytoca clinical isolates, collected in within 2015–2018 period in medical institutions in St. Petersburg. Two K. oxytoca and two Raoultella ornithinolytica clinical strains displaying typical properties were used as a control. The presence of 5-aminosalicylate decarboxylase was detected by the chromogenic reaction with the “Klebsiella 5-ASK CHROME C” nutrient medium (Pasteur Institute, St. Petersburg). Substrate utilization as the sole carbon source was detected on a solid minimal synthetic medium added with 2 g/L substrate during incubation for 72 hours at 37°C. Biochemical bacteria features were studied by the microvolume method with the “Rapid-Entero” test system (Pasteur Institute, St. Petersburg). Genetic strain characterization was performed by estimating 16S rRNA, gyrA, rpoB by using a routine PCR with primer sequences described before. Two rpoB gene fragments with a total length 834 bp, 16S rRNA gene fragment — 387 bp, and gyrA gene fragment — 441 bp were amplified followed by their sequencing by Singer on an ABI 3130 automatic capillary sequencer (Applied Biosystems, USA) and subsequently determined similarity levels. Amplification pattern for pehX gene PCR fragments was performed by using a method described elsewhere with two primer pairs flanking fragment AD with a 513 bp length and 344 bp CD-long motifs. While examining 11 clinical bacterial strains identified earlier as Klebsiella oxytoca, lacking (atypical, negative) a 5-aminosalicylate decarboxylase (detected by the chromogenic reaction by 5-aminosalicylic acid) unique for the genus Klebsiella, molecular techniques identified 9 K. michiganensis strains and 1 strain highly homologous to Klebsiella kielensis based on the rpoB gene nucleotide sequence, confirming its high informative value. We used the methods for estimating a similarity level for sequenced fragments of 16S rRNA genes (fragment length 387 bp), gyrA gene (fragment length 441 bp), rpoB gene (rpoB-b and rpoB-e with a total fragments length 834 bp), and the analysis of marker amplicon patterns for pehX gene (AD, CD). It was shown that for the 4 K. oxytoca strains, 99–100% similarity to K. michiganensis was identified for all fragments in the sequenced genes. Moreover, similarity of all 9 strains detected with K. michiganensis was revealed only in the rpoB gene, hereby allowing to recommend it as the most informative approach. The pehX gene encoding polygalacturonase was verified by PCR in the majority of K. michiganensis strains, pointing that this approach is not rational for their identification (distinguish with K. oxytoca). The most informative for the phenotypic identification of K. michiganensis are were assays characterized by a common profile for the majority of strains: lack of 5-aminosalicylate decarboxylase, lack of utilized histamine, dulcitol, tricarballylic acid; positive for indole production, as well as D-melezitose and putrescine utilization.